Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can anyone help me show that the following equations are equivalent?

$$x-\ln|1+e^x| = -\ln|e^{-x}+1|$$

I'm having a little trouble. It should be an easy solution, where I take one equation, start with it, and show that it can turn into the opposing one. I know it involves the properties of logs, but I am just stuck on it.

I got both the equations when solving for the anti-derivative of $1/(1+e^x)$, and am under the impression they are the same, but I do not understand how. I can show my work for this if it would help, just ask. Thank you.

Little help? Would appreciate any insight.

share|cite|improve this question

Hint: Try starting with $x=\ln(e^x)$ on the left side, to get $$\ln(e^x)-\ln(1+e^x) = -\ln(e^{-x}+1)$$ How can you use properties of logarithms to manipulate the left side further?

share|cite|improve this answer

$$x-\ln|1+e^x|=-(-x+\ln|1+e^x|)$$ $$=-(\ln e^{-x}+\ln|1+e^x|)=-\ln(e^{-x}\cdot|1+e^x|) $$ $$=-\ln|e^{-x}+1|.$$ Above we used $a=\ln e^a$ and $\ln a+\ln b=\ln ab$.

share|cite|improve this answer

Well, if those at the argument of the logarithms are absolute values, you can get rid of them since both $1+e^x$ and $1+e^{-x}$ are greater than $0$. On the other hand $$-\log(1+e^{-x})=\log\left(\frac{1}{1+e^{-x}}\right)=\log\left(\frac{e^x}{1+e^x}\right)=x-\log(1+e^x).$$

share|cite|improve this answer

Note that $e^{-x}+1$ is always positive, as is $1+e^x$, so the absolute value bars are really irrelevant.

Then just do some algebra and use properties of the logarithm: $$\begin{align*} -\ln|e^{-x}+1| &= -\ln\left(\frac{1}{e^x} + 1\right)\\ &= -\ln\left(\frac{1+e^x}{e^x}\right)\\ &= \ln\left( \left(\frac{1+e^x}{e^x}\right)^{-1}\right)\\ &= \ln\left(\frac{e^x}{1+e^x}\right)\\ &= \ln(e^x) - \ln(1+e^x)\\ &= x - \ln(1+e^x)\\ &= x - \ln|1+e^x|. \end{align*}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.